4D printing of magnetic smart structures based on light-cured magnetic hydrogel - Deng, Chengyao; Qu, Juntian; Dong, Jiahao; Guo, Yifei; Wu, Xinze; Fang, Yi; Sun, Xudong; Wei, Yijian; Li, Zhenkun (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
•This paper developed a magnetic hydrogel that can be 4D printed. Our work provides a solution for the integration of structural and functional properties in soft robots and fills the gap in the field of 4D printing of magnetic hydrogels.•Unlike conventional hydrogels used for 3D printing, we added bentonite to the printing ink to thicken it, making it easier to print with a stable yield stress, and preventing the aggregation and settling of internal magnetic particles.•Instead of the conventional magnetic domain programming method, we incorporated a large capacitor into the circuit to magnetize the printing ink through the charging and instantaneous discharging of the capacitor. This integrated the material pre-treatment process with the programming process, rather than magnetizing the material first and then programming the printing in the printer.•In this paper, we created various soft actuators with different structures to achieve different functions, exploring practical applications. In recent years, with the development of materials science, various new materials that can sense external stimuli and respond have emerged. This ability to respond to external stimuli enables these materials to empower other materials or structures, greatly promoting the development of soft robots. In recent years, many 4D printed magnetic silicon gels have appeared, while 4D printing of magnetic hydrogels is still a blank slate. Here, we have developed a light-curable magnetic hydrogel that can be 4D printed. Unlike traditional methods of thickening hydrogels for 3D printing, we added bentonite to thicken the printing ink and controlled its rheological properties to make it suitable for printing. During the printing process, we used capacitive momentary discharge to generate a strong magnetic field to program the printing ink, eliminating the need for pre-treatment of the printing ink. We also studied the influence of the content of ferromagnetic particles and the size of the external magnetic field on its responsiveness. Finally, we printed and programmed the hydrogel on a silicone sheet to empower the silicone sheet. Based on this, we have created a variety of different types of soft actuators to achieve different movements and functions.